Single incision laparoscopic appendectomy: A prospective study - Mangam, Nilesh P (Asian Journal of Medical Sciences, 2021)
Background: Appendicitis is one of the common pathologies encountered in surgical practice. Except in minority of the cases, the treatment is usually surgical. Till recent past, open appendectomy has been the procedure of choice for appendicitis. With increasing expertise in laparoscopic surgeries more and more surgeons are utilizing the laparoscopic approach for appendectomy. Laparoscopic surgeries have distinct advantages such as less surgical trauma, improved and quick postoperative recovery, and esthetic results. Single-incision laparoscopic surgery (SILS) is rapidly gaining acceptability in young population because of its cosmetic advantages. Moreover, these surgeries also avoid the risk of port-site hernias and the possibility of wound infection. Aims and Objective: The purpose of this study is to present our initial experience with this surgery using a single incision laparoscopic appendectomy (LA) using conventional instruments. Materials and Methods: This was a prospective cohort study conducted in the department of surgery of a tertiary care medical college situated in an urban area. The duration of the study was 2 years. All adult patients diagnosed to be having uncomplicated appendicitis and undergoing appendectomy by SILS were included in this study on the basis of a predefined inclusion and exclusion criteria. Pre-operative data collected included age, sex, weight, duration of complaint, concomitant medical conditions (like ischemic heart disease, chronic obstructive airway disease, diabetes mellitus, pancreatitis, and liver cirrhosis) and previous upper or lower abdominal surgery. All patients were treated by SILS except 1 patient in whom the procedure was converted to open surgery. Mean surgical time, Intraoperative procedure details and postoperative complications were studied in all the cases. p < 0.05 was taken as statistically significant. Statistical analysis was done using SSPS 21.0 software. Results: Out of 30 patients in this study 26 patients were female and 4 patients were male. The male to female ratio was found to be 1:6.15. Mean age of studied cases was found to be 26.2 years. Operative time required for the first 15 cases in an average was 120.00 min however it was reduced for the next 15 cases was 73.73 min. Overall time required in an average was 96.86 min. Out of 30 cases, The procedure was completed with Single Incision LA in 23 Patients, i.e., 76.6 %. In the initial cases, we started with two 5 mm and one 10mm port. To reduce crowding we replaced the 5 mm port to 3 mm port. The 10 mm port was also replaced by 5 mm in the past few cases in 1 patient the procedure was converted to open surgery. The analysis of postoperative complications showed that five patients had Post-Operative wound Infection. One patient had post-operative peritonitis. Conclusion: SILS is a feasible and safe surgical method for appendectomy and is being increasingly preferred particularly by young patients due to its excellent cosmetic results.